PROLIFERAÇÃO DE CÉLULAS GLIAIS DE RETINA EMBRIONÁRIA DE PINTO EM CULTURA: MODULAÇÃO POR FATORES PROVENIENTES DE CÉLULAS MAIS DIFERENCIADAS - França, Guilherme Rapozeiro (2009)
ATP is emerging as an important mitogen in the developing retina. Here, we show that the response of chick retinal cells to this nucleotide decreases as cells differentiate in culture. Both nonstimulated or ATP-induced proliferative response of these cells was consistently attenuated if cycling cells were cocultured with cells from older embryos or if they were cultured with conditioned medium from postmitotic cells. The effect of conditioned medium was dose-dependent and reversible. Removal of conditioned medium from the cultures increased both basal and ATP-induced incorporation of [3H]-thymidine. The effect of conditioned medium was also dependent on the developmental stage of the retina used to prepare the medium. Conditioned medium from cells of retinas of 8- or 9-day-old embryos completely inhibited the proliferative response induced by ATP, as well as the proliferative activity of cells cultured without this nucleotide. Similar inhibition of ATP-induced increase in [3H]-thymidine incorporation was observed using conditioned medium from purified glial cultures, although basal incorporation of [3H]-thymidine was not affected. Incubation of cells with conditioned medium for 24 h completely abolished the formation of [3H]-phosphoinositides induced by ATP. This effect was blocked by the P2 receptor antagonist PPADS, suggesting that agonist-dependent desensitization of P2 receptors occured in the cultures incubated with conditioned medium from postmitotic cells. However, removal of small molecules such as nucleotides by dialysis did not affect the decline in the proliferative activity induced by conditioned medium, suggesting that additional mechanisms contribute to conditioned medium-dependent cell cycle arrest of early developing retinal cells in culture. Taken together, our results suggest that factors that induce the arrest of glial cells in the mitotic cycle are released from postmitotic cells. The arrest of the cells is concomitant with agonist-dependent P2 receptor desensitization.